2020
DOI: 10.1186/s12935-020-1112-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells derived from iPSCs expressing interleukin-24 inhibit the growth of melanoma in the tumor-bearing mouse model

Abstract: Background: Interleukin-24 (IL-24) is a therapeutic gene for melanoma, which can induce melanoma cell apoptosis. Mesenchymal stem cells (MSCs) show promise as a carrier to delivery anti-cancer factors to tumor tissues. Induced pluripotent stem cells (iPSCs) are an alternative source of mesenchymal stem cells (MSCs). We previously developed a novel non-viral gene targeting vector to target IL-24 to human iPSCs. This study aims to investigate whether MSCs derived from the iPSCs with the site-specific integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, the limitations observed with the widespread use of UCBT are in part due to their delay in the replenishment of the hematopoietic microenvironment and the immune competency to overcome the original disorder (Algeri et al, 2020). The MSCs, apart from their use as cell-based therapies in regenerative medicine, are reported to have both pro-or anti-cancer properties, either in their naïve state or after being engineered to carry apoptotic inducers or small molecules (Hmadcha et al, 2020;Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitations observed with the widespread use of UCBT are in part due to their delay in the replenishment of the hematopoietic microenvironment and the immune competency to overcome the original disorder (Algeri et al, 2020). The MSCs, apart from their use as cell-based therapies in regenerative medicine, are reported to have both pro-or anti-cancer properties, either in their naïve state or after being engineered to carry apoptotic inducers or small molecules (Hmadcha et al, 2020;Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As the stromal progenitor cells, their role in tumor progression and TME is being put under the spotlight of tumor researches. Most studies have confirmed the tumorcontributing role of MSC, while the anti-tumor effect of MSC gradually unveils in several cancer types such as melanoma; glioma; HCC (92)(93)(94). Also, there are opposite results clarifying that MSC from human adipose tissue and the umbilical cord could inhibit GC progression and induce apoptosis of cancer cells (95,96).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have showed iMSCs presented traditional three-lineage differentiation capacity, including osteocytes, chondrocytes and adipocytes. For example, antibody-mediated osseous regeneration (AMOR) has been proved as a promising strategy for osteogenic differentiation of iMSCs [ 24 , 28 ]; Jungbluth et al, has indicated iMSCs combined with calcium phosphate granules (CPG) showed greater role in critical-size defects in the proximal tibias of mini-pigs in the early phase of bone healing compared to that of autologous bone marrow derived MSCs or CPG alone [ 29 ]. Holding the mesoblast lineage cell differentiation capacity of iMSCs is well described, but the ability of transdermal differentiation of iMSCs is still unexplored.…”
Section: Introductionmentioning
confidence: 99%